Relationship between etiology and covert cognition in the minimally conscious state - Cruse, D; Chennu, S; Chatelle, C; Fernández-Espejo, D; Bekinschtein, T A; Pickard, J D; Laureys, S; Owen, A M (Neurology, 2012)
Functional neuroimaging has shown that the absence of externally observable signs of consciousness and cognition in severely brain-injured patients does not necessarily indicate the true absence of such abilities. However, relative to traumatic brain injury, nontraumatic injury is known to be associated with a reduced likelihood of regaining overtly measurable levels of consciousness. We investigated the relationships between etiology and both overt and covert cognitive abilities in a group of patients in the minimally conscious state (MCS). Twenty-three MCS patients (15 traumatic and 8 nontraumatic) completed a motor imagery EEG task in which they were required to imagine movements of their right-hand and toes to command. When successfully performed, these imagined movements appear as distinct sensorimotor modulations, which can be used to determine the presence of reliable command-following. The utility of this task has been demonstrated previously in a group of vegetative state patients. Consistent and robust responses to command were observed in the EEG of 22% of the MCS patients (5 of 23). Etiology had a significant impact on the ability to successfully complete this task, with 33% of traumatic patients (5 of 15) returning positive EEG outcomes compared with none of the nontraumatic patients (0 of 8). The overt behavioral signs of awareness (measured with the Coma Recovery Scale-Revised) exhibited by nontraumatic MCS patients appear to be an accurate reflection of their covert cognitive abilities. In contrast, one-third of a group of traumatically injured patients in the MCS possess a range of high-level cognitive faculties that are not evident from their overt behavior.